Fluorescence Lifetime of Actin in the FHC Transgenic Heart - Mettikolla, P. (2009)
Clinical studies have revealed that the D166V mutation in the ventricular myosin regulatory light chain (RLC) can cause a malignant phenotype of familial hypertrophic cardiomyopathy (FHC). It has been proposed that RLC induced FHC in the heart originates at the level of the myosin cross-bridge due to alterations in the rates of cross-bridge cycling. In this report we examine whether the environment of an active cross-bridge in cardiac myofibrils from transgenic (Tg) mice is altered by the D166V mutation in RLC. The cross-bridge environment was monitored by tracking the fluorescence lifetime (τ) of Alexa488-phalloidin labeled actin. The fluorescence lifetime is the averaged rate of decay of a fluorescent species from the excited state, which strongly depends on various environmental factors. We observed that the lifetime was high when cross-bridges were bound to actin and low when they were dissociated from it. The lifetime was measured every 50 msec from the center half of the I-band during 60 sec of rigor, relaxation and contraction of muscle. We found no differences between lifetimes of Tg-WT and Tg-D166V muscle during rigor, relaxation and contraction. The duty ratio expressed as a fraction of time that cross-bridges spend attached to the thin filaments during isometric contraction was similar in Tg-WT and Tg-D166V muscles. Since independent measurements showed a large decrease in the cross-bridge turnover rate in Tg-D166V muscle compared to Tg-WT, the fact that the duty cycle remains constant suggests that the D166V mutation of RLC causes a decrease in the rate of cross-bridge attachment to actin.